Pendugaan Evapotranspirasi Bulanan Tanaman Padi Sawah dengan Menggunakan Model Simulasi Tanaman di Kabupaten Jayawijaya Provinsi Papua - Yitenus Tabuni; Jelie Viekson Porong; Johannes E.X. Rogi (COCOS, 2017)
ABSTRACT   Rice is the second staple supplies in Jayawijaya Regency of Papua product beside Sweet potato. The area of rice plant is 250 ha, with production of 655 tons (BPS data from the Department of Agriculture of Food Crops and Horticulture of Papua Province 2014). The total area of Jayawijaya Regency is 13,925.31 km2 which is administratively divided into 40 districts with 4  Kelurahan, and 328 Villages. The Population area 241. 280 inhabitants. Most of the people live on slope of the hills  whith are difficult to reach and are of temhisby long dryness. The estimation of the evapotranspiration in this research uses a plant simulation model. The purpose of this simulation model has advantages, among others, does not require a long time to utilize the results and cost efficient in terms of cost. This study aims to estimate the monthly evapotranspiration of wetland rice crops in Jayawijaya Regency Papua Province by using shierary rice.Ve2 2, 1. The results of research can be used as a tool for cultivating rice crops especially for water management. The growth model is a simple representation of the plant growth system described in the mathematical model and analyzed statistically. The advantages are derived from the using of model simulations, that such as can shorten the time to predict the potential of crop production.  Keywords: Evapotranspiration estimation of field and model results